Characteristics of Hair and Beard in Theater Makeup - Jalilova Feruza Suratovna (Zien Journals, 2023)
In this article, the artistic process associated with hairdressing is considered as a separate art form. The modeling and artistic design of hairstyles, the creation of a composition, the creation of a form are considered theoretically, and practical recommendations are given.
Keywords: Artistic process; vision; art